The Private and Social Utility of Extortion - Conybeare, John A. C. (American Economic Review, 1981)
A recent exchange between George Daly and J. Fred Giertz and Harold Demsetz focused attention on the social efficiency of extortion. Daly and Giertz suggested that extortion could be defined as ... the of obtaining payments from some entity in return for not imposing upon that entity some harmful effect, where the generator of the external effect receives no direct net internal benefit from the act (p. 998). Extortion is, they say, an which merely redistributes income and reduces social welfare by the amount of any transaction costs. It is thus distinguished from legitimate bargaining, which will produce social welfare gains. Demsetz replied to this argument by pointing out that there are many activities which might result in social welfare gains but are, nevertheless, prohibited as extortionary acts. The legality of a threat bears only a very rough relationship to the social utility of the act, and the definition of extortion is therefore rather than economic, according to Demsetz. The difference between these two positions relates to the definition of the extortionary itself. If A demands property from B under threat to accuse B of a crime, extortion has occurred. The which is being threatened may have individual utility to A of equal to or less than zero, as Daly and Giertz correctly point out. There may also be a net gain in social utility either if the threat is of some value to society (for example, it may help deter crime) or if the property transferred is worth more to A than to B (for example, perhaps because of unequal marginal utilities). Thus, an economic interpretation of extortion must be more narrowly defined as the threat to commit an which by itself would not materially benefit the actor alone. Daly and Giertz are correct in postulating the existence of an economic definition of extortion consistent with current legal practice, though wrong in their inferences about its direct social (rather than individual) utility. Demsetz correctly points out that individual acts of extortion may have positive social utility effects, but incorrectly concludes that any definition of extortion must therefore be legalistic. The following discussion indicates that legal theory is broadly consistent with an individual utility interpretation of extortion. It is only the delimitation of the benefits of the threatened extortionary act, not the definition of extortion, which is purely a legalistic question. English criminal law, as embodied in the Larceny Act (1916), specified blackmail (used synonomously with the term extortion) as ... the demanding of any person with menaces, and without reasonable or probable cause, any property or valuable thing .. (see J. W. C. Turner, p. 312). Such menaces include: threats to accuse another of a crime, unlawful violence or restraint, threats to publish and, in general, any threat that ... should produce in any ordinary man such a degree of fear or alarm as would unsettle his mind (Turner, p. 315). The distinction sought in the is whether there is a clear nexus between the threatened and the property demanded, and whether there is value by itself in the threatened, the degree of nexus being one criterion for judging the latter. G. L. Williams' survey of English law on blackmail provides ample evidence of the legal pursuit of this distinction, particularly the emphasis on the private utility of the extortionary itself. He refers to the Dymond case in 1920, which provided the modern English precedent. In this case, a girl who alleged that she had been indecently assaulted wrote to the man in question demanding money under threat of adverse publicity about his moral character. She was convicted of blackmail on the grounds that *Australian Graduate School of Management, University of New South Wales. This note has benefited from comments by an anonymous reviewer and from references supplied by Kenneth Ove.